Non-invasive diagnostic methods for investigating the quality of Žilina airport’s runway - SLABEJ, Martin; GRINČ, Michal; KOVÁČ, Matúš; DECKÝ, Martin; ŠEDIVÝ, Stefan (Contributions to Geophysics and Geodesy, 2015)
The Žilina airport was after almost 50 years of use measured by non-invasive methods including GPR and Profilograph GE in order to investigate the quality of the runway pavement at the chosen spots. Since it was just a pilot action, a sample of survey was carried out. The testing spots were placed where the geologic drill core J02 have been drilled out. The measurements performed by Profilograph GE were used to verify the quality of the pavement surface in term longitudinal unevenness by means of index IRI and C. The GPR survey was performed in 3D geometry, hence in the x- and y-direction. A horn type antenna with central frequency of 2 GHz was used on the test field in order to verify the thicknesses of pavement construction layers. Here, the result of a 3D survey is presented. The investigation confirms two sub-horizontal construction layers of the runway pavement. In some areas the GPR interpretation was not possible due to the signal attenuation. This significant signal attenuation is found mainly in the areas where the linear cracks are situated.